Microstructure formation and mechanical properties of ODS steels built by laser additive manufacturing of nanoparticle coated iron-chromium powders. (March 2021) - Doñate-Buendia, C.; Kürnsteiner, P.; Stern, F.; Wilms, M.B.; Streubel, R.; Kusoglu, I.M.; Tenkamp, J.; Bruder, E.; Pirch, N.; Barcikowski, S.; Durst, K.; Schleifenbaum, J.H.; et al.
Abstract: Oxide dispersion strengthened (ODS) steels are known for their enhanced mechanical performance at high temperatures or under radiation exposure. Their microstructure depends on the manufacturing process, from the nanoparticle addition to the base steel powder, to the processing of the nanoparticle enriched powder. The optimization and control of the processing steps still represent a challenge to establish a clear methodology for the additive manufacturing of ODS steels. Here, we evaluate the microstructure, nanoparticle evolution, and mechanical properties of ODS steels prepared by dielectrophoretic controlled adsorption of 0.08 wt% laser-synthesized yttrium oxide (Y2 O3 ) on an iron-chromium ferritic steel powder (PM2000). The influence of the ODS steel fabrication technique is studied for two standard additive manufacturing techniques, directed energy deposition (DED) and laser powder bed fusion (LPBF). The compressive strength of the ODS steels at 600 °C is increased by 21% and 29% for the DED and LPBF samples, respectively, compared to the DED and LPBF steels manufactured without Y2 O3 nanoparticle addition. The Martens hardness is enhanced by 9% for the LPBF ODS steel while no significant change is observed in the DED ODS steel. The microstructure and nanoparticle composition and distribution are evaluated by electron backscatter diffraction, scanning electron microscopy–energy-dispersive X-ray spectroscopy, and atom probe tomography, to compare the microstructural features of DED and LPBF manufactured parts. Smaller grain size and more homogeneous distribution with lower agglomeration of Y-O nanoparticles in the LPBF sample are found to be key factors for enhanced mechanical response at 600 °C. The enhanced mechanical properties of the LPBF-processed sample and the more homogeneous nanoparticle dispersion can be linked to results obtained by finite element methods simulations of the melt pool that show two orders of magnitude faster cooling rates for LPBF than for DED. Therefore, this work presents and validates a complete laser-based methodology for the preparation and processing of an ODS steel, proving the modification of the microstructure and enhancement of the high-temperature strength of the as-built parts. Graphical asbstracts: Image, graphical abstract